Swarm Intelligence-Based Learning Management for Enhancing the Quality of Arabic Language Learning: إدارة التعلم القائمة على الذكاء الجماعي في تحسين جودة تعلم اللغة العربية - Herman, Herman; Arani, Samsuar; Mukhlizar, Mukhlizar (Institut Agama Islam Negeri Lhokseumawe, 2025)
This study aims to examine and analyze the swarm-based learning management model in enhancing the quality of Arabic language learning, focusing on the development of collaboration, communication, adaptation, flexibility, critical and creative thinking skills, as well as the integration of digital technology in the Arabic learning process. The research employs a library research method using a literature review approach to analyze data and information related to swarm-based learning management in enhancing Arabic learning quality. The findings indicate that swarm-based learning management is implemented through the following stages: The first stage involves determining the components of swarm-based learning management, which include setting learning objectives, grouping students, organizing the learning environment, utilizing digital technology, scheduling, and evaluation. The second stage involves defining the steps of swarm-based learning management, including initiation, grouping, task organization, supervision, and evaluation. The third stage involves establishing strategies for swarm-based learning management, including project-based learning strategies, research-based learning strategies, and case-based learning strategies. The results of this study are expected to provide new insights for educators and educational practitioners in the field of Arabic language education to develop more relevant and effective learning strategies in the current era of the Industrial Revolution 4.0.